2009
DOI: 10.1007/s12160-009-9127-2
|View full text |Cite
|
Sign up to set email alerts
|

Mediators Affecting Girls’ Levels of Physical Activity Outside of School: Findings from the Trial of Activity in Adolescent Girls

Abstract: Background Providing after school activities is a community level approach for reducing the decline in physical activity of girls as they reach early adolescence. Purpose The purpose of this study was to examine psychosocial, environmental, and behavioral factors as potential mediators of after school physical activity in adolescent girls. Methods We assessed objectively measured levels of physical activity occurring outside of school and potential predictors and mediators of activity in girls participatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 41 publications
8
68
0
3
Order By: Relevance
“…Specifically, friend support was found to be the source of support most highly related to physical activity in both lunchtime and after-school settings. Previous studies have demonstrated similar findings on moderate-to-vigorous physical activity during nonschool-time and mean daily physical activity in adolescent girls [11,[35][36][37][38]. Collectively, findings suggest that developing strategies to encourage or assist with friends' physical activity behaviors can be beneficial in promoting physical activity in adolescent girls, regardless of contexts.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Specifically, friend support was found to be the source of support most highly related to physical activity in both lunchtime and after-school settings. Previous studies have demonstrated similar findings on moderate-to-vigorous physical activity during nonschool-time and mean daily physical activity in adolescent girls [11,[35][36][37][38]. Collectively, findings suggest that developing strategies to encourage or assist with friends' physical activity behaviors can be beneficial in promoting physical activity in adolescent girls, regardless of contexts.…”
Section: Discussionsupporting
confidence: 65%
“…Compared with friend support, support from family and teachers for physical activity were found to be less important in both contexts. This finding is understandable because adolescent girls are becoming independent from family and strengthening their identification with peers [11,37]. Interestingly, the effect of family support on physical activity was significant in the after-school context but not at lunch time.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that school-based PA interventions increased students' PA participation during school days (Kriemler et al, 2010;Loucaides, Jago, & Charalambous, 2009;Tammelin, Laine, & Turpeinen, 2013) out-ofschool (Lytle et al, 2009; Nemet et al, 2005;Nilsson et al, 2009), physical capacity (Sollerhed & Ejlertsson, 2008;Kalaja, 2012), active commuting to school (Tammelin, Laine, & Turpeinen, 2013), total daily PA (de Bourdeaudhuij et al, 2010;Harrison et al, 2006;Jurg et al, 2006;McManus et al, 2008;Metcalf et al, 2012;Schneider, Dunton, & Cooper, 2008;Pate et al, 2005), perceived PA effort in PE , and positive attitudes toward physical activities (Christodoulos et al, 2006;. For instance, in a school-based PA program involving a sample of 498 Grade 1 and 5 children in Switzerland, in-school MVPA increased from 38 minutes to 45 minutes per day, while out-of-school activity decreased from 67 minutes to 61 minutes per day during one school year.…”
Section: School-based Physical Activity Interventionsmentioning
confidence: 98%
“…Previous research has found that PE motivation is a key factor underlying PA Hagger et al, 2003; and corresponds to transfer of behavior across contexts for greater total PA Hagger, 2014;Kalaja, 2012;. Several scholars have advocated that schools should place a higher priority on encouraging young people to engage greater daily physical activity, especially out-of-school (e.g., Flohr, Todd, & Tudor-Locke;Hagger et al, 2009;Lytle et al, 2009). Furthermore, a number of interventions have shown school-based PA interventions to be successful in terms of health related outcomes (Dobbins et al, 2013;Strong et al, 2005) and PA engagement (e.g., Carrell et al, 2005;Schneider Jamner et al, 2004;Simon et al, 2004;Ward, 2011;Webber et al, 2008).…”
mentioning
confidence: 99%
“…If I were to be physically active during my free time on most days it would help me spend more time with friends) on 5-point scales ranging from 'Disagree a lot' (1) to ' Agree a lot' (5); and corresponding value statements (e.g. spending time with my friends is…), on 5-point scales ranging from 'Very unimportant' (1) to 'Very important' (5) [54]. The outcome-expectancy value items were formed as a product of the belief and corresponding value item scores [55].…”
Section: Methodsmentioning
confidence: 99%